2022
DOI: 10.2967/jnumed.121.263255
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Reactive Astrogliosis with 18F-SMBT-1 Across the Alzheimer Disease Spectrum

Abstract: Background: Neuroinflammatory reaction in Alzheimer's disease (AD) brains involves reactive astrocytes which overexpress monoamine oxidase-B (MAO-B). 18 F-SMBT-1 is a novel F-18 PET tracer highly selective for MAO-B. We characterized the clinical performance of 18 F-SMBT-1 PET across the Alzheimer's disease (AD) continuum as a potential surrogate marker of reactive astrogliosis Methods: We assessed 18 F-SMBT-1 PET regional binding in 77 volunteers (76±5.5 y.o.; 41F/36M) across the AD continuum: 57 cognitively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 57 publications
2
32
0
Order By: Relevance
“…Astrocyte transcriptome analysis of AD brain tissue revealed gene changes associated with Aβ and pTau pathology in inflammation, protein regulation, oxidative stress, antioxidant function, lipid metabolism, and ion homeostasis (Viejo et al, 2022). Positron emission tomography (PET) and magnetic resonance imaging (MRI) (Choo et al, 2014;Vilemagne et al, 2022a) revealed dynamic changes in reactive astrocytes and Aβ due to mild cognition impairment. At preclinical stages, astrogliosis was induced by early Aβ deposition and loss of gray matter cells (Choo et al, 2014;Vilemagne et al, 2022a), whereas astrocyte atrophy appeared subsequently with greater Aβ deposition (Hsu et al, 2018).…”
Section: Astrocytes and Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Astrocyte transcriptome analysis of AD brain tissue revealed gene changes associated with Aβ and pTau pathology in inflammation, protein regulation, oxidative stress, antioxidant function, lipid metabolism, and ion homeostasis (Viejo et al, 2022). Positron emission tomography (PET) and magnetic resonance imaging (MRI) (Choo et al, 2014;Vilemagne et al, 2022a) revealed dynamic changes in reactive astrocytes and Aβ due to mild cognition impairment. At preclinical stages, astrogliosis was induced by early Aβ deposition and loss of gray matter cells (Choo et al, 2014;Vilemagne et al, 2022a), whereas astrocyte atrophy appeared subsequently with greater Aβ deposition (Hsu et al, 2018).…”
Section: Astrocytes and Alzheimer's Diseasementioning
confidence: 99%
“…Positron emission tomography (PET) and magnetic resonance imaging (MRI) (Choo et al, 2014;Vilemagne et al, 2022a) revealed dynamic changes in reactive astrocytes and Aβ due to mild cognition impairment. At preclinical stages, astrogliosis was induced by early Aβ deposition and loss of gray matter cells (Choo et al, 2014;Vilemagne et al, 2022a), whereas astrocyte atrophy appeared subsequently with greater Aβ deposition (Hsu et al, 2018). Astroglia tracer also revealed that reactive astrogliosis increased and reached a peak in preclinical stages of AD, followed by a decrease of astrogliosis and then rise again in dementia stages, exerting neurotoxic functions (Kumar et al, 2021).…”
Section: Astrocytes and Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Removing senescent glial cells prevented tau-dependent pathology and cognitive decline in PS19 mice [111]. Early astrocytosis has been demonstrated by positron emission tomography tracers in both patients with AD and amyloidosis animal models [112][113][114][115][116][117][118]. Tau accumulates in hilar astrocytes of the dentate gyrus in postmortem brains from patients with AD [119][120][121] and induces neuronal dysfunction and memory deficits in a mouse model [122].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies of [ 18 F]SMBT-1 demonstrated that high binding affinity and high binding selectivity to MAO-B with low non-specific binding as well as good PK and metabolic profiles (Harada et al, 2021). Preliminary cross-sectional human PET studies in a wide range of ages are indicating that [ 18 F]SMBT-1 is a selective MAO-B tracer with low non-specific binding, high entry into the brain while displaying favorable reversible kinetics, and have significantly higher binding in Aβ + AD (Figure 4) and Aβ + cognitively unimpaired controls (Villemagne et al, 2022), similarly to what has been reported with plasma GFAP (Verberk et al, 2020;Chatterjee et al, 2021). These findings suggest that reactive astrogliosis as measured by MAO-B through [ 18 F]SMBT-1 is associated with early Aβ accumulation, providing strong support for its use as surrogate marker of astrogliosis.…”
Section: Recent Progress In the Development Of Novel Monoamine Oxidas...mentioning
confidence: 98%